PANDANGAN ISLAM TENTANG PERNIKAHAN DINI - HASANAH, USWATUN (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2014)
Early marriage or marriage under the age of crowded discussed by many people in this country. Actually, in fiqh or Islamic law there is no minimum age limit of marriage. Jumhur or the majority of scholars say that the guardian or parent must marry off their daughters at any age. However, due to considerations of beneficiaries, some scholars memakruhkan practice of early marriage. Makruh means may be better left yet. Young girls are not physically and psychologically ready to assume duties as a wife and homemaker, although she had Aqeel baligh or already through the menstrual period. On this occasion the author mengungkapa normative concept of the view early marriage, in this case in view of Islam.